2007
DOI: 10.1057/palgrave.ejis.3000695
|View full text |Cite
|
Sign up to set email alerts
|

Why the old world cannot publish? Overcoming challenges in publishing high-impact IS research

Abstract: We review the status of European publishing in high-impact Information System (IS) journals finding that the European publication record is disappointing. We consider popular explanations to this state of affairs and find them neither credible nor useful for improving the European record. We propose several constructive reasons for this including (1) the lack of appreciation of the article genre, (2) weak publishing cultures, (3) inadequate Ph.D. preparation for article publishing, (4) weak reviewing practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 10 publications
(8 reference statements)
2
74
1
1
Order By: Relevance
“…Journal editors in particular often must be happy if they manage to recruit a sufficient number of reasonably qualified reviewers who are ready to do the job. Yet, one should always keep in mind that reviewers act as significant gatekeepers in science (Lyytinen, Baskerville, Iivari, & Te'eni, 2007). Their reports essentially affect not only editorial decisions on the submitted papers but, sometimes, the authors' future and, in the longer run, the direction of the journal will take and the respective field as a whole.…”
Section: My Personal Experiences As a Reviewer And As An Authormentioning
confidence: 99%
“…Journal editors in particular often must be happy if they manage to recruit a sufficient number of reasonably qualified reviewers who are ready to do the job. Yet, one should always keep in mind that reviewers act as significant gatekeepers in science (Lyytinen, Baskerville, Iivari, & Te'eni, 2007). Their reports essentially affect not only editorial decisions on the submitted papers but, sometimes, the authors' future and, in the longer run, the direction of the journal will take and the respective field as a whole.…”
Section: My Personal Experiences As a Reviewer And As An Authormentioning
confidence: 99%
“…IS is methodologically plural, and researchers draw on different paradigms such as interpretivism, positivism, and critical realism, and apply a multitude of different research methods (Benbasat and Weber 1996). While prior debates have suggested that IS should favor certain methods and certain research approaches (Lyytinen et al 2007;Ö sterle et al 2010), our study suggests that the community of inquirers appreciates a diversity of methods and paradigms, and sees a challenge in better understanding how they relate to and complement each other. This is consistent with the idea of ''disciplined methodological Scale: 1 = strongly disagree; 2 = disagree; 3 = undecided; 4 = agree; 5 = strongly agree pluralism'' (Landry and Banville 1992).…”
Section: Meta Challenges For Developing the Is Disciplinementioning
confidence: 95%
“…Another strategy is to find a top international journal with a European culture, which to me means respectful of author's identity, in terms of culture. Respecting this publishing culture does not mean not asking authors to be focused on a clear set of related research questions when presenting their ideas, or encouraging a poetic style, but it should respect different types of contributions, some emphasizing practical aspects, and not oppose the broad literature and/or philosophy to normal science as it is sometimes implied (Lyytinnen et al 2007). …”
Section: Bise-related Research In Spain: a Personal Viewmentioning
confidence: 99%